2014
DOI: 10.30843/nzpp.2014.67.5742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culture medium light and air circulation on sporulation of <i>Neonectria ditissima</i>

Abstract: In culture most isolates of Neonectria ditissima the causal organism of European canker do not produce conidia Those that do often produce singlecelled conidia rather than the typical multicelled conidia that are found in nature A series of experiments was conducted to determine the conditions needed for conidium production Four culture media (malt extract agar modified Matsushimas medium (MM) apple sap amended water agar (ASAWA) and water agar) five light regimes including darkness near ultra violet (NUV) lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In previous pathogenicity trials using single conidium isolates of N. ditissima in both glasshouse (Scheper et al 2010) and field studies , trees inoculated with different inocula also developed lesions that varied in number and lesion size. Scheper et al (2014) also showed that the isolates used in this study were very different, with regard to sporodochia production on agar and conidial morphology. The most pathogenic isolate RS324p was the only isolate that produced sporodochia on water agar, while the almost nonpathogenic isolate RS305p produced significantly fewer multi-celled conidia (1.8%) than did either the other two isolates or the field inoculum (56.5-86.0%).…”
Section: Figurementioning
confidence: 74%
See 1 more Smart Citation
“…In previous pathogenicity trials using single conidium isolates of N. ditissima in both glasshouse (Scheper et al 2010) and field studies , trees inoculated with different inocula also developed lesions that varied in number and lesion size. Scheper et al (2014) also showed that the isolates used in this study were very different, with regard to sporodochia production on agar and conidial morphology. The most pathogenic isolate RS324p was the only isolate that produced sporodochia on water agar, while the almost nonpathogenic isolate RS305p produced significantly fewer multi-celled conidia (1.8%) than did either the other two isolates or the field inoculum (56.5-86.0%).…”
Section: Figurementioning
confidence: 74%
“…Three single ascospore isolates, RS305p, RS324p and RS401p2, isolated from cankers with mature perithecia in Lower Moutere (Nelson), New Plymouth (Taranaki) and Upper Moutere (Nelson) were grown on Matsushima's medium (MM, Matsushima 1961) as adjusted by Dubin & English (1974) for 3 weeks at 20°C under continuous near ultraviolet light, as described by Scheper et al (2014). The isolates were selected because of their morphological differences.…”
Section: Production Of Conidial Suspensionsmentioning
confidence: 99%
“…Mockinoculated potted trees of each accession, treated with 0.005% Tween®20 (Tween solution), were placed randomly between the inoculated buckets and trees, as were buckets with mock-inoculated dormant shoots (not included in the analysis). Inoculum was prepared using conidia grown on Matsushima's medium under continuous near-UV light as described by Scheper et al (2014). The conidial suspension (7.5×10 4 conidia mL -1 in Tween solution) was prepared by mixing conidia from 12 N. ditissima isolates ( Table 1).…”
Section: Trial Design and Inoculationmentioning
confidence: 99%
“…Neonectria ditissima isolates and spore production Eight isolates of N. ditissima (RS324p, RS304p1, RS305p, RS307p1, RS340p1, RS347c, MW14c, ICMP14098) were used in this study, as described by Scheper et al 2014. Conidia were produced on modified Matsushima agar (MM) at 20°C under near-UV light in non-vented Petri dishes, as described by Scheper et al 2014. Ascospores were produced by crossing RS324p with the other seven isolates using a method adapted from Scheper & Pauli (2013), using glucose yeast agar and sterile 'Royal Gala' wood pieces placed on the agar.…”
Section: Methodsmentioning
confidence: 99%